2020
DOI: 10.1101/2020.07.14.202085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

10 years of EPOC: A scoping review of Emotiv’s portable EEG device

Abstract: BACKGROUND Commercially-made low-cost electroencephalography (EEG) devices have become increasingly available over the last decade. One of these devices, Emotiv EPOC, is currently used in a wide variety of settings, including brain-computer interface (BCI) and cognitive neuroscience research. PURPOSE The aim of this study was to chart peer-reviewed reports of Emotiv EPOC projects to provide an informed summary on the use of this device for scientific purposes. METHODS We followed a five-stage methodologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 376 publications
0
19
0
Order By: Relevance
“…Research techniques that were once possible only with expensive EEG setups are now achievable using low-cost alternatives ( Sawangjai et al, 2020 ; Williams, McArthur & Badcock, 2020 ). One of these techniques is the event-related potential (ERP) approach.…”
Section: Introductionmentioning
confidence: 99%
“…Research techniques that were once possible only with expensive EEG setups are now achievable using low-cost alternatives ( Sawangjai et al, 2020 ; Williams, McArthur & Badcock, 2020 ). One of these techniques is the event-related potential (ERP) approach.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, consumer EEG systems have attracted the attention of researchers. For example a recent scoping review of Emotiv EPOC applications found 382 journal articles and conference proceedings published from 2009 to 2019, including 51 experimental research studies and 31 validation studies ( Williams, McArthur & Badcock, 2020 ). Debener et al (2012) were among the first to investigate the utility of EPOC when they removed the amplifier from its original case and attached it to research-quality electrodes that were inserted into an EasyCap® (Herrsching, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…The Emotiv Epoc is a portable, high-resolution EEG system with 14 dry electrodes designed to be quick and easy to fit, taking practical application measurements. Many BCI studies used EPOC to control or interact with machines in users’ environments [ 92 ], although the validity of Emotiv products in clinical research is still a matter of debate.…”
Section: Mi-based Bcw Elementsmentioning
confidence: 99%